PENERAPAN METODE K-MEANS CLUSTERING DALAM PENGELOMPOKAN STATUS KESEHATAN IBU HAMIL (STUDI KASUS: Bidan Praktek Mandiri Sri Mulyati, Am.Keb) - Dona; Rifqi, Mirajul; Nurhabibah (Riau Journal Of Computer Science, 2020)
Overall maternal health conditions such as the age of pregnant women, gestational age also participate in influencing fetal growth, the article there are several diseases that can affect pregnancy and fetal development if not addressed and not routinely examined. Currently the growth problem is also an international target listed in the SDGs (Sustainable Development Goals) to reduce the incidence of short and thin children under five until 2025. This study aims to determine maternal health during pregnancy, which is assessed by nutritional intake during pregnancy and weight gain third trimester maternal body with the growth of children under five in the area of Suka Maju Hamlet, Pematang Tebih Village, Rokan Hulu Regency. The results of this study can be used as an evaluation material to improve the quality of maternal health status during pregnancy and reduce the risk of growth disorders in children under five in the community